RESEARCH OF INFLUENCE ON DISTRIBUTION OF RADIO WAVES IN CITY OF PROFILE OF HIS BUILDING - D. A. Zatuchny; J. V. Slad (Научный вестник МГТУ ГА)
N this article influence is investigated on distribution of radio waves in the municipal terms of height and building closeness. A model over of distribution of radio waves is brought from an aircraft side. Charts over of dependence of probability of arrival of signal are brought from airship from the height of flight and middle number of building.